1978
DOI: 10.1128/jb.135.3.1162-1164.1978
|View full text |Cite
|
Sign up to set email alerts
|

Control of Escherichia coli growth by CO2

Abstract: Escherichia coli B dependence on CO2 for growth was demonstrated. At suboptimal CO2 concentrations the rate of growth was controlled by CO2 concentration. Many techniques used to minimize the lag period preceding culture growth were described in the early microbiological literature, whereas others are a part of the legacy of unpublished observations from many laboratories. The appearance of a lag period after successive transfers of cultures in the same medium always was an enigma that has been subject to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 9 publications
(14 reference statements)
1
19
0
Order By: Relevance
“…To test this explanation, the ability of filtrates from early exponential phase cultures to reduce lag was examined (data not shown); however, the lag reductions observed were no greater than could be predicted on the basis of their acetaldehyde content (and, to a small extent, their slightly reduced pH compared to fresh medium), suggesting that the proposed additional lag-reducing substance may have been lost during filtration and storage. It is possible that the inoculum size effects under these conditions reflect the need to accumulate carbon dioxide in the medium prior to growth: a strong correlation between extracellular carbon dioxide and lag times in bacteria has previously been demonstrated by several workers (Gladstone et al, 1935;Repaske et al, 1974, Repaske andClayton, 1978;Walker, 1932). A similar effect would be expected for S. cerevisiae which conducts various carboxylation reactions (Strathern et al, 1982).…”
Section: Is Acetaldehyde Excretion Responsible For the Inoculum Size mentioning
confidence: 68%
“…To test this explanation, the ability of filtrates from early exponential phase cultures to reduce lag was examined (data not shown); however, the lag reductions observed were no greater than could be predicted on the basis of their acetaldehyde content (and, to a small extent, their slightly reduced pH compared to fresh medium), suggesting that the proposed additional lag-reducing substance may have been lost during filtration and storage. It is possible that the inoculum size effects under these conditions reflect the need to accumulate carbon dioxide in the medium prior to growth: a strong correlation between extracellular carbon dioxide and lag times in bacteria has previously been demonstrated by several workers (Gladstone et al, 1935;Repaske et al, 1974, Repaske andClayton, 1978;Walker, 1932). A similar effect would be expected for S. cerevisiae which conducts various carboxylation reactions (Strathern et al, 1982).…”
Section: Is Acetaldehyde Excretion Responsible For the Inoculum Size mentioning
confidence: 68%
“…In aerobic glucose-based bioprocesses the endogenous production of CO 2 is typically sufficiently high to promote microbial growth even at low cell densities. However, it is a well-known fact that anaerobic growth of some bacteria, like E. coli , requires the external supply of CO 2 /HCO 3 - to avoid long lag phases (26, 55, 56). The critical impact of CO 2 /HCO 3 - levels may become especially evident under conditions when the endogenous CO 2 production rate becomes limiting.…”
Section: Discussionmentioning
confidence: 99%
“…The dependence of bacteria on the presence of CO 2 for growth or for overcoming long lag times (the so-called sparking phenomenon) has been known for 25 years [92,93]. At low pCO 2 and low rates of metabolism, CO 2 is expected to di¡use out of the cell faster than it is hydrated to HCO 3 3 , thereby depleting the intracellular HCO 3 3 needed for carboxylation reactions.…”
Section: E Colimentioning
confidence: 99%
“…At low pCO 2 and low rates of metabolism, CO 2 is expected to di¡use out of the cell faster than it is hydrated to HCO 3 3 , thereby depleting the intracellular HCO 3 3 needed for carboxylation reactions. Previous studies have shown that either a large inoculum or the presence of succinate, aspartate or oxaloacetate can overcome the long lag times observed during growth at low pCO 2 by increasing the citric acid cycle rates and the concentration of CO 2 and HCO 3 3 [92,93]. Kozliak et al [91] showed that the growth of wild-type E. coli and the cynS, cynT and cynTSX deletion mutants is negligible when CO 2 is absent from the atmosphere.…”
Section: E Colimentioning
confidence: 99%